HUBUNGAN POLA MAKAN TERHADAP KEJADIAN SINDROM DISPEPSIA PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS BAITURRAHMAH ANGKATAN 2018 - Rifkind Malik; Irsal Munandar; Irwandi, Irwandi; Masdarul Ma'arif; Lusi Syafitri (Yayasan Nusantara Hasana Berdikari, 2023)
Dyspepsia is a complaints of complaints or a collection of symptoms (syndromes) consisting of pain or discomfort in the epigastrium, nausea, vomiting, bloating, rapid pain, full stomach, and belching. One of the causes of dyspepsia, due to dietary factors caused by irregular eating patterns. This research to regulate the diet with the occurrence of dyspeptic syndrome in students of the Faculty of Medicine, Baiturrahmah University class of 2018. The type of this research is a correlative analytic study with a cross sectional approach. The population of this study were students of the Faculty of Medicine, Baiturrahmah University class of 2018 with 130 samples of total sampling technique. Data analysis using Chi Square test. There were 85 respondents (65.4%) who experienced dyspepsia, as many as 106 people (81.5%) who ate well, 109 (83.8%) rarely consumed spicy food, 119 people (91.5%) rarely consume acidic foods, and 123 people (94%) rarely consume irritating (carbonated) drinks. There is no relationship between eating frequency and the incidence of dyspeptic syndrome with a value of p = 0.261, there is no relationship between types of spicy, acidic or irritating (carbonated) drinks with p value = 0.254. There is no relationship between dyspepsia syndrome and diet among students of the Faculty of Medicine, Baiturrahmah University class of 2018.